FOVEAL SPARING INTERNAL LIMITING MEMBRANE PEELING FOR IDIOPATHIC MACULAR HOLES: EFFECTS ON ANATOMICAL RESTORATION OF THE FOVEA AND VISUAL FUNCTION. Issue 11 (November 2020) - Murphy, Declan C.; Fostier, Will; Rees, Jon; Steel, David H.
Abstract : Purpose: Muller cells seem to be important in maintaining foveal morphology through connections between their foot processes and the internal limiting membrane (ILM). Internal limiting membrane peeling causes Muller cell trauma. We hypothesized that leaving a rim of unpeeled ILM around idiopathic macular holes undergoing vitrectomy surgery would improve postoperative foveal morphology and vision. Methods: Prospective pilot study of fovea-sparing ILM peeling in a consecutive cohort of patients with macular holes over a 12-month period. Spectral-domain optical coherence tomography and Early Treatment Diabetic Retinopathy Study letters best-corrected visual acuity were assessed preoperatively and postoperatively, and foveal morphology and metamorphopsia postoperatively. The foveal sparing group was compared with a second consecutive cohort who received standard ILM peeling (control group). Results: Thirty-four eyes of 34 patients were included in each group. Groups showed no significant preoperative differences. 34/34 holes were successfully closed with surgery in the foveal sparing group and 32/34 in the control group. The foveal sparing group showed better postoperative best-corrected visual acuity (67.7 vs. 63.8, P = 0.003) and best-corrected visual acuity improvement (25.1 vs. 20.2, P = 0.03). The foveal sparing group demonstrated thicker minimum foveal thickness (211 vs. 173 μ m, P = 0.002) and less steep foveal depression (158 vs. 149, P = 0.002). Conclusion: Preserving nonpeeled ILM around macular holes resulted in a high closure rate, improved foveal morphology, and better postoperative best-corrected visual acuity. An appropriately powered randomized controlled study is warranted. Abstract : Preserving nonpeeled internal limiting membrane around idiopathic macular holes during surgery results in high macular hole closure rates, and improved postoperative foveal morphology and vision compared with complete internal limiting membrane peeling as per usual practice. This may be due to improved maintenance of Muller cell integrity and foveal shape reformation.